KEBERADAAN RAYAP TANAH (Macrotermes gilvus ) DAN PERTUMBUHAN TANAMAN KARET DI KEBUN KARET RAKYAT YANG DIKELOLA SECARA ALAMI : SUATU CONTOH PENGELOLAAN KEBUN BERWAWASAN LINGKUNGAN - Zainal Arifin (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
TherResearch to determine the effect of the existence of soil termite nests (Macrotermes gilvus) on the growth of rubber plants is carried out in smallholder rubber gardens which are managed with local wisdom, naturally without using chemical fertilizers and pesticides. The area of rubber plantations studied was around 2 ha. In the rubber garden soil, many soil termite nests were found which identified M. gilvus species. The parameters of the study were stem circumference, which was measured using a tape meter at a tree height of 125cm from the ground surface, while the percentage of rubber tree canopy cover was measured using the Line Intercept tape method. Data analysis used the Mann-Whitney test. Samples of rubber trees with termite nests are the closest trees to the location of termite nests, while trees without termite nests are rubber trees which at a minimum radius of 3 m are not found termite nests. Organic garden management without pesticides allows termites to be present and nest in the garden. The existence of soil termites M. gilvus (Hagen) lodged in rubber plantation land has caused changes in physico-chemical characteristics / soil fertility, this is evident from the differences in the growth of stem circumference and better canopy cover on rubber plants that grow near termite nests compared to growing on soil without termite nests. Keywords: Macrotermes gilvus, rubber gardens, growth, stem circumference, termite nests